Reṇu se bheṇṭa : Phaṇīśvaranātha Reṇu se bheṇṭavārttāoṃ kā saṅkalana - Reṇu, Phaṇīśvaranātha (Vāṇī Prakāśana, 1987)
Transcript of interviews with Phaṇīśvaranātha Reṇu, Hindi writer, about his life and career as a writer.